2022
DOI: 10.1186/s12913-022-07547-9
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction can co-exist with hesitation: qualitative analysis of acceptability of telemedicine among multi-lingual patients in a safety-net healthcare system during the COVID-19 pandemic

Abstract: Background The COVID-19 pandemic triggered unprecedented expansion of outpatient telemedicine in the United States in all types of health systems, including safety-net health systems. These systems generally serve low-income, racially/ethnically/linguistically diverse patients, many of whom face barriers to digital health access. These patients’ perspectives are vital to inform ongoing, equitable implementation efforts. Methods Twenty-five semi-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…Our findings match the results shown by Kaur et Al., who showed that respondents expressed 84-100% agreement to telemedicine health service provided for management of hyperthyroidism [16]. Similarly other researchers also have shown high satisfaction of patients who used telemedicine health service during pandemic [17][18][19].…”
Section: Discussionmentioning
confidence: 81%
“…Our findings match the results shown by Kaur et Al., who showed that respondents expressed 84-100% agreement to telemedicine health service provided for management of hyperthyroidism [16]. Similarly other researchers also have shown high satisfaction of patients who used telemedicine health service during pandemic [17][18][19].…”
Section: Discussionmentioning
confidence: 81%
“…Pre-COVID-19 concerns about acceptability of this modality of health care delivery appear to be somewhat allayed. 15,16 Previous barriers Telehealth service rendered via asynchronous telecommunications system GT Telehealth service rendered via interactive audio and video telecommunication systems related to the comfort of patients or providers with mental health care delivery through telehealth in particular may have been overcome during this pandemic-initiated system change. 1,14 The ability of telehealth services for mental health conditions to fit flexibly and easily into busy lives may have an impact on staying power.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-COVID-19 concerns about acceptability of this modality of health care delivery appear to be somewhat allayed. 15,16 Previous barriers related to the comfort of patients or providers with mental health care delivery through telehealth in particular may have been overcome during this pandemic-initiated system change. 1,14 The ability of telehealth services for mental health conditions to fit flexibly and easily into busy lives may have an impact on staying power.…”
Section: Discussionmentioning
confidence: 99%